PENGARUH ANIL TERMAL TERHADAP BESARAN OPTIS LAPISAN TIPIS a-SiC:H HASIL METODE DC SPUTTERING I. TARGET SILIKON - Saleh, Rosari; Munisa, Lusitra; Marianty, Dewi (UI Scholars Hub, 2003)
The Effect of Thermal Annealing on the Optical Properties of a-SiC:H Films Produced by DC Sputtering Methods: I. Silicon Target Case. The effects of thermal annealing treatment on the optical properties of amorphous silicon carbon films deposited by silicon target in an argon, methane and hydrogen gas mixture have been studied using ultra violet-visible (uv-vis) spectroscopy. Both n and α, and consequently the real and imaginary parts of the dielectric constant, show a considerable variation with subsequent annealing up to annealing temperature 500 °C, with the most rapid changes occurring for temperature 300 °C. The films tend denser as the annealing temperature increased up to 500 °C. The optical gap improved slightly upon annealing, where as the disorder of the amorphous network reduced. The annealing treatment produces reorganization of the amorphous network since thermal annealing results in dissociation of hydrogenated bonds (Si-H and C-H).